Mediterranean Region Encyclopedia - A. V. Semenov; I. S. Zonn (Проблемы постсоветского пространства, 2021)
The Mediterranean Sea consisting of numerous seas is enclosed by three continents — Europe, Asia and Africa. It is a specific phenomenon in terms of geography, oceanology and world history. This is the only place in the world where many cultures and civilizations mutually enriching each other and giving to the world the benchmarks for development have appeared and alternated. As E. Bradford wrote “Each part of the Mediterranean Sea is really specific. One is apt to violence, other is more serene, the third is prone to periodical outbursts of fervor, the fourth is dangerous and unpredictable as schizophrenic.” The therapy of nature and man that lasted for many centuries has played its positive role having turned the Mediterranean into the center of trade, fishery and tourism. The countries surrounding the sea (there are twenty-one of them) are well described and well known that is why we concentrate on eleven water areas each of which makes a part in the general Mediterranean Sea puzzle.The factor of the sea improves our perception of the land-sea interface and this can be described in such comprehensive scientific and popular publication as encyclopedia. Today when Russia with all its navy power returns to the World Ocean, in particular to the Mediterranean, using its renovated Mediterranean fleet the extension of navigation knowledge in this water area which had always been in the focus of tsars, emperors and presidents of Russia becomes a very important factor.